Komunikasi Pemasaran sebagai Upaya Rebuilding Image Pizza Hut Restoran di Masa Pandemi Covid-19 - Nur Iksan; Imaddudin; Fadli M. Athalarik (Jurnal Komunikasi Nusantara, 2022)
The Covid-19 pandemic has made the F&B (food and beverage) sector also spin its brains to defend itself from market share. In addition, the concept changes with policies that must be adapted to the competition in the middle of the market. The purpose of this study was to determine the promotion strategy used in rebuilding the image of Pizza Hut during the Covid-19 pandemic. This research is descriptive qualitative, with data collection methods by observation, interviews and documentation which is processed by the data from reducing data to explaining based on findings and correlation of concepts and theories used. The results of the study describe the use of the 7P marketing mix (product, price, place, promotion, people, process and physical evidence) in a promotional strategy that supports the rebuilding of Pizza Hut's image, with a focus on approach to people and products. People who will continue to communicate directly with consumers, and the product becomes a Pizza Hut signature that should not be left behind. The concept of picking up consumers, promotions by lowering prices and other processes that support Pizza Hut promotions. So that the original image as a family restaurant with dining at the place is now closer to consumers and affordable prices for all levels of society and can be achieved not only in related restaurants but can be found in various strategic places while still showing the characteristics of Pizza Hut itself. Abstrak Kondisi Pandemi Covid-19 menjadikan sektor F&B (food and beverage) juga berputar otak untuk tetap mempertahankan dari pangsa pasar. Selain itu, perubahan konsep dengan kebijakan yang harus di adaptasi berdampak pada perebutan pasar ditengah persaingan. Tujuan penelitian ini untuk mengetahui strategi promosi yang digunakan dalam rebuilding image Pizza Hut di masa pandemic Covid-19. Penelitian ini secara kualitatif deskriptif, dengan metode pengumpulan data secara observasi, wawancara dan dokumentasi yang diolah data-data tersebut dari mereduksi data hingga memaparkan berdasarkan temuan dan korelasi konsep dan teori yang digunakan. Hasil penelitian menggambarkan penggunaan bauran pemasaran 7P (product, price, place, promotion, people, process dan physical evidence) dalam strategi promosi yang menunjang rebuilding image Pizza Hut, memfokuskan pendekatannya pada people dan produk. People yang akan mengkomunikasikan langsung kepada konsumen, dan produk tetap menjadi signature Pizza Hut yang tidak boleh ditinggalkan. Konsep jemput konsumen, promosi dengan banting harga serta proses lain yang mendukung promosi Pizza Hut. Sehingga image semula sebagai family restaurant with dining at the place kini menjadi lebih dekat dengan konsumen dan harga yang terjangkau bagi semua lapisan masyarakat serta bisa dijangkau bukan hanya di resto terkait namun bisa ditemukan diberbagai tempat strategis dengan tetap menunjukkan ciri khas dari Pizza Hut itu sendiri.